2018
DOI: 10.1016/j.neuroimage.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of white matter bundles using local and global streamline-based registration and clustering

Abstract: Virtual dissection of diffusion MRI tractograms is cumbersome and needs extensive knowledge of white matter anatomy. This virtual dissection often requires several inclusion and exclusion regions-of-interest that make it a process that is very hard to reproduce across experts. Having automated tools that can extract white matter bundles for tract-based studies of large numbers of people is of great interest for neuroscience and neurosurgical planning. The purpose of our proposed method, named RecoBundles, is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
200
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 231 publications
(215 citation statements)
references
References 42 publications
1
200
0
Order By: Relevance
“…Automatic segmentation methods are becoming more widespread. Methods such as, but not limited to, (Chekir, Descoteaux, Garyfallidis, Côté, & Boumghar, 2014;Garyfallidis et al, 2017;Guevara et al, 2011;O'Donnell et al, 2017;O'donnell, Golby, & Westin, 2013;Wassermann et al, 2016;Wasserthal, Neher, & Maier-Hein, 2018;Yendiki et al, 2011;Zhang et al, 2018) aim to simplify the work of raters. The typical standard of most automatic segmentation method is to reach the accuracy of raters, thus it is crucial to truly quantify human reproducibility in manual tasks.…”
Section: Quantifying Reproducibility In Tractographymentioning
confidence: 99%
See 2 more Smart Citations
“…Automatic segmentation methods are becoming more widespread. Methods such as, but not limited to, (Chekir, Descoteaux, Garyfallidis, Côté, & Boumghar, 2014;Garyfallidis et al, 2017;Guevara et al, 2011;O'Donnell et al, 2017;O'donnell, Golby, & Westin, 2013;Wassermann et al, 2016;Wasserthal, Neher, & Maier-Hein, 2018;Yendiki et al, 2011;Zhang et al, 2018) aim to simplify the work of raters. The typical standard of most automatic segmentation method is to reach the accuracy of raters, thus it is crucial to truly quantify human reproducibility in manual tasks.…”
Section: Quantifying Reproducibility In Tractographymentioning
confidence: 99%
“…Some measures related to streamlines require the datasets to be exactly the same, for example, Dice score, as streamline reconstructions are sets of discrete points with floating point coordinates and not discrete grids like 3D images. For this reason, comparison of streamlines is more challenging and datasets that do not originate from the same source distance in millimeters is often the only available solution (Garyfallidis et al, ; Maier‐Hein et al, ). Automatic segmentation methods are becoming more widespread.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two popular strategies for automated white matter parcellation (O'Donnell, Golby, & Westin, ): (a) fiber clustering that groups white matter fibers according to their geometric trajectories, aiming to reconstruct tracts corresponding to the white matter anatomy (Ding, Gore, & Anderson, ; Garyfallidis et al, ; Garyfallidis, Brett, Correia, Williams, & Nimmo‐Smith, ; Guevara et al, ; Jin et al, ; Kumar, Desrosiers, Siddiqi, Colliot, & Toews, ; O'Donnell & Westin, ; Prasad et al, ; Siless, Chang, Fischl, & Yendiki, ; Visser, Nijhuis, Buitelaar, & Zwiers, ; Wassermann, Bloy, Kanterakis, Verma, & Deriche, ; Zhang, Wu, Norton, ) and (b) cortical‐parcellation‐based that parcellates tractography according to a cortical parcellation, focusing on the structural connectivity among different brain regions of interest (ROIs) (Bassett & Bullmore, ; Bastiani, Shah, Goebel, & Roebroeck, ; Bullmore & Sporns, ; Gong et al, ; Ingalhalikar et al, ; Sporns et al, ; Wakana et al, ; Wassermann et al, ; Yeh, Badre, & Verstynen, ; Zalesky et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Unsupervised streamline-based methods, such as those in Brun et al (2004); Maddah et al (2005); O' Donnell and Westin (2007); Guevara et al (2012); Tunç et al (2014); Siless et al (2016); Zhang et al (2018), perform whole brain segmentation through clustering, without prior knowledge about the anatomy of the bundles and without leveraging examples of expert-made segmented bundles, limiting the quality of segmentation. In contrast, supervised streamline-based methods require one or more examples of the bundle to learn from, in order to segment such bundle in the target subject, such as those in Mayer et al (2011); Olivetti and Avesani (2011); Vercruysse et al (2014); Yoo et al (2015); Labra et al (2016); Garyfallidis et al (2018) and Sharmin et al (2018). It has been shown that streamline-based methods like those presented in Garyfallidis et al (2018), referred to as RecoBundles, and in Sharmin et al (2018), referred to as LAP, outperform connectivity based methods in terms of quality of segmented bundles.…”
Section: Introductionmentioning
confidence: 99%